Craniopharyngioma in the third ventricle: necropsy findings and histogenesis. Issue 8 (August 1987) - Kunishio, K; Yamamoto, Y; Sunami, N; Asari, S; Akagi, T; Ohtsuki, Y
Abstract : A case of craniopharyngioma confined within the third ventricle with necropsy is reported. A stalk-like structure in this tumour was present in the wall of the third ventricle at its base. It is suggested that this tumour might have arisen from the remnants of Rathke's pouch persisting in the tuber cinereum.